2021
DOI: 10.1002/edn3.227
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in bacterial communities on uniform substrates in non‐wadeable rivers

Abstract: Undertaking environmental assessments on non‐wadeable rivers is challenging due to their size, depth, and water velocity. The cotton strip assay (CSA) is a functional indicator used in assessing the ecological health of non‐wadeable rivers by measuring cellulose decomposition potential. Enhancing knowledge on the microbial communities responsible for decomposition would assist in developing a microbial‐based biotic index that could complement the CSA. The aims of this study were to explore the temporal and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Metabarcoding resulted in more than 18,000 bacterial ASVs, of which the 429 most frequent, comprising 75% of the total relative abundance represented over 15 different bacterial phyla. This work adds to the growing field of genetic characterization of bacterial communities for indicators of ecological or environmental conditions in streams and can inform the future applications of bacterial indicators in monitoring programs [ 26 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabarcoding resulted in more than 18,000 bacterial ASVs, of which the 429 most frequent, comprising 75% of the total relative abundance represented over 15 different bacterial phyla. This work adds to the growing field of genetic characterization of bacterial communities for indicators of ecological or environmental conditions in streams and can inform the future applications of bacterial indicators in monitoring programs [ 26 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding has become a valuable tool for gathering extensive amounts of microbial community data that would have been very costly or nearly impossible a few years ago [30][31][32][33][34]. Recent studies in freshwater environments have shown bacterial assemblage responses to nutrients [26,35,36], flow and fine sediment [37], temperature and pH [36], and conductivity [35].…”
Section: Introductionmentioning
confidence: 99%